Parametric Study on the Removal of Lead and Recovery as Lead Carbonate in Simulated Lead Acid Battery Industry Wastewater - Roselle Y. Mamuad; Angelo Earvin Sy Choi; Ming-Chun Lu (Chemical Engineering Transactions)
Lead (Pb) is notorious for its elevated and persistent toxicity, even at extremely low concentrations, posing limitations on the reusability and recyclability of industrial wastewater. This investigation focused on extracting Pb from simulated lead acid battery industry wastewater in the form of Lead Carbonate (PbCO3) granules through the fluidized-bed homogeneous granulation process. Achieving a Pb granulation efficiency of 97.55 % and total removal efficiency of 99.67 % required maintaining the operating pH within the 9.4-9.6 range, coupled with a carbonate-to-lead molar ratio of 1:1 and an initial concentration of 2600 ppm for 72 h reaction time. Most of the recovered crystals are less than 0.42 mm in size. This study highlights the potential for Pb recovery as PbCO3 from contaminated wastewater using fluidized-bed granulation technology.